SAT0609-HPR DELPHI CONSENSUS FOR THE OPTIMAL TREATMENT & MANAGEMENT OF COMPLEX RHEUMATOID ARTHRITIS (RA) PATIENTS. (2nd June 2020) - Dulay, G.; Choy, E.; Barnes, T.; Chagadama, D.; Cole, Z.; Malaviya, A.; Robinson, S.; Walker, D.; Daly, C.; Savill, N.; Warren, T.; Williams, N.
Abstract : Background: A significant proportion of patients with rheumatoid arthritis (RA) have additional considerations that must be taken into account for managing their disease. 1 These include; co-morbidities, extra-articular manifestations and poor prognostic factors. 2-5 Tailored management could reduce the burden on patients, the health system and wider society. The 'complex' RA patient group is ill-defined and no specific recommendations exist for their optimal management and treatment. Objectives: A group of UK Rheumatology experts aimed to provide a set of recommendations to support consistent and high quality management, grounded in current evidence, expert opinion and best practice. Methods: A steering group meeting identified priority topics associated with complex RA. Conclusion: These recommendations are offered: Healthcare professionals (HCPs) should consider a patient's complexity (including clinical co-morbidities, extra-articular manifestations and poor prognostic factors) prior to making treatment decisions; HCPs should take into account a patient's psychosocial factors and health literacy prior to making treatment decisions; Patient specific outcomes for complex RA should always be proactively agreed with the individual and/or their carers; The local healthcare system should consider the overall costs of complex RA, beyond drug acquisition costs to allow flexibility of prescribing choices, as necessary in this group of patients; Local treatment pathways should reflect that treatments with particular modes of action are more suitable for individual patients with complex RA. Management of complex RA patients should extend beyond guidelines and recognise additional sources of evidence including; clinical studies, Real World Experience (RWE) and post-marketing surveillance. References: [1]Uhlig T, Moe RH, Kvien TK. The burden of disease in rheumatoid arthritis. Pharmacoeconomics 2014;32:841–51 [2]Dougados M, et al. Ann Rheum Dis 2014;73:62–68. [3]Parodi M et al, Rheumatism, 2005, 57(3): 154-60. [4]Young A & Koduri G. Best Pract Res Clin Rheumatol. 2007 Oct;21(5):907-27. [5]Holroyd CR, et al. Rheumatology 2019;58:e3-e42 Acknowledgments: Support for medical writing/editorial assistance, provided by Tim Warren at Triducive was funded by Roche Products Ltd. & Chugai Pharma Ltd. in accordance with Good Publication Practice (GPP3) guidelines (http://www.ismpp.org/gpp3 ). Disclosure of Interests: Gurdeep Dulay Grant/research support from: Educational grants to attend congress meetings/conferences from Roche, Chugai, UCB, Internis, Pfizer, Lilly, Sandoz, Consultant of: Honoraria for advisory board services from Roche, Chugai, Novartis, Speakers bureau: Speaker fees from Roche, Chugai, Novartis, Amgen, Lilly, Sandoz, Ernest Choy Grant/research support from: Amgen, Bio-Cancer, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer, Roche, UCB, Consultant of: AbbVie, Amgen, AstraZeneca, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chelsea Therapeutics, Chugai Pharma, Daiichi Sankyo, Eli Lilly, Ferring Pharmaceuticals, GlaxoSmithKline, Hospita, Ionis, Janssen, Jazz Pharmaceuticals, MedImmune, Merck Sharp & Dohme, Merrimack Pharmaceutical, Napp, Novartis, Novimmune, ObsEva, Pfizer, R-Pharm, Regeneron Pharmaceuticals, Inc., Roche, SynAct Pharma, Sanofi Genzyme, Tonix, UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Chugai Pharma, Eli Lilly, Hospira, Merck Sharp & Dohme, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Sanofi-Aventis, UCB, Theresa Barnes Consultant of: Ad boards for Roche, Actelion and Abbvie, Speakers bureau: Speaker for MSD, UCB, Pfizer, Abbvie, Actelion, Roche and BMS, Debbie Chagadama Consultant of: Roche, Chugai, BI, Speakers bureau: Roche, Chugai, BI, Zoe Cole Consultant of: Consultancy work for Roche, Lilly, Gilead, Abbvie, Pfizer, UCB, Speakers bureau: Lilly, BMS, Abbvie, Pfizer, UCB, Janssen, Anshuman Malaviya Consultant of: Roche, Chugai, MSD, Pfizer, Novartis, Lily, BMS, Speakers bureau: Roche, BMS, Pfizer, MSD, Sandra Robinson Consultant of: Eli Lilly for Education Nurse Meeting, David Walker Grant/research support from: Gilead, Consultant of: Gilead, Lilly, Pfizer, Roche, Speakers bureau: Lilly, Pfizer, Roche, Chris Daly Employee of: Roche, Nicola Savill Employee of: Roche, Tim Warren Consultant of: Roche, Employee of: AstraZeneca, Nick Williams Shareholder of: MSD, Consultant of: Roche, Employee of: MSD